If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -5)(x + 6) = 0 Reorder the terms: x(-5 + 2x)(x + 6) = 0 Reorder the terms: x(-5 + 2x)(6 + x) = 0 Multiply (-5 + 2x) * (6 + x) x(-5(6 + x) + 2x * (6 + x)) = 0 x((6 * -5 + x * -5) + 2x * (6 + x)) = 0 x((-30 + -5x) + 2x * (6 + x)) = 0 x(-30 + -5x + (6 * 2x + x * 2x)) = 0 x(-30 + -5x + (12x + 2x2)) = 0 Combine like terms: -5x + 12x = 7x x(-30 + 7x + 2x2) = 0 (-30 * x + 7x * x + 2x2 * x) = 0 (-30x + 7x2 + 2x3) = 0 Solving -30x + 7x2 + 2x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-30 + 7x + 2x2) = 0 Factor a trinomial. x((-6 + -1x)(5 + -2x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 3
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {0, -6, 2.5}
| -3G-5=6G+40 | | x+2x+8=772 | | y=2(-1)2+3 | | 8y-20=-6y+50 | | -4(2b+3)+(9b-5)=0 | | 3(x+10)-0.07(x-40)=8.1 | | -5k+5=25 | | 3x-8=-32 | | 7v^2+4=-29v | | 1x-5x^2=0 | | -9+-8= | | 1.4q-3.1-4.7q=4.3q-4.7 | | 5(x+9)+4=-6(x-9)-7 | | b^2-4b=02 | | -8=3t+6 | | 14x-4(9x-40)=355 | | m^2=45 | | 5p-24=-28+3p | | y=-0.8x+6 | | x-2+2=1 | | m^2+20m-85=-4 | | 20-x=19-2x | | 2m-5=20-3m | | x=-6+2x^2 | | 10-(-4r)=30 | | 2n^2+9n=-4 | | 4x+6=-58 | | -24+12=m-2 | | x+2=4x(x-3) | | 90+2x=180 | | 2m-(4m+12)=6 | | 5-5y+y-1=-23 |